IMPLEMENTING LARAVEL FOR DIGITAL PAYMENT AUTOMATION IN ISLAMIC BOARDING SCHOOLS THROUGH THE WATERFALL APPROACH - Erna Kumalasari Nurnawati; Muhammad Zidan Rifqi Ramadhan; Edhy Sutanta; Renna Yanwastika Ariyana (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Effective financial management is essential for ensuring the optimal operation of educational institutions, including the Al Luqmaniyyah Islamic Boarding School in Yogyakarta. Traditional manual financial administration often leads to delayed reporting, inaccurate record-keeping, and limited accountability. To address these challenges, this study emphasizes the digitalization of payment processes through the development of a web-based digital payment information system that supports structured student billing management, including scheduled and monthly bills, as well as fully digitized payment transactions. The system was developed using the Software Development Life Cycle (SDLC) Waterfall model, employing Laravel version 11 and a MySQL database. It integrates multi-role authentication features using the Spatie Laravel Permission package to ensure secure and differentiated access. System validation was conducted through Black Box Testing with the Equivalence Partitioning technique, focusing on verifying functional correctness across core modules such as billing management, payment processing, and role-based access control. The testing process was carried out after system implementation in a production environment to ensure that application behavior aligned with predefined functional requirements. The results indicate that all system modules function in accordance with the specified design, achieving full functional validation. The digitalization of payment processes significantly simplifies financial transaction recording, minimizes administrative errors, and enhances transparency for both administrators and students. This study highlights the importance of payment digitalization in modernizing financial services in Islamic boarding schools and is expected to serve as a reference for similar system development initiatives in other pesantren environments.